2019
DOI: 10.3390/cancers11101480
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms of Escape from BRAF Oncogene Dependency

Abstract: About eight percent of all human tumors (including 50% of melanomas) carry gain-of-function mutations in the BRAF oncogene. Mutated BRAF and subsequent hyperactivation of the MAPK signaling pathway has motivated the use of MAPK-targeted therapies for these tumors. Despite great promise, however, MAPK-targeted therapies in BRAF-mutant tumors are limited by the emergence of drug resistance. Mechanisms of resistance include genetic, non-genetic and epigenetic alterations. Epigenetic plasticity, often modulated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 165 publications
(216 reference statements)
0
25
0
Order By: Relevance
“…In addition to signaling network adaptations and resistance mutations in a targeted molecule, epigenetic alterations seem to play similarly important roles in drug resistance. Due to the extensive characterization of acquired RAF inhibitor resistance in malignant melanoma, the involvement of epigenetic mechanisms and resistance to targeted therapies is best understood in these cancers [180].…”
Section: Epigenetics and Drug Resistancementioning
confidence: 99%
“…In addition to signaling network adaptations and resistance mutations in a targeted molecule, epigenetic alterations seem to play similarly important roles in drug resistance. Due to the extensive characterization of acquired RAF inhibitor resistance in malignant melanoma, the involvement of epigenetic mechanisms and resistance to targeted therapies is best understood in these cancers [180].…”
Section: Epigenetics and Drug Resistancementioning
confidence: 99%
“…6B). Indeed, sensitivity to BRAF and MEK inhibitors, a feature of BRAF addiction, has been associated with distinct phenotype plasticity of the differentiation state and global alterations in gene expression programs in BRAF-mutated melanomas [30][31][32] . Further, it has been reported that a gene expression pattern associated with epithelial-mesenchymal transition (EMT) correlates with KRAS addiction 16 .…”
Section: Discussionmentioning
confidence: 99%
“…The raF/MeK/erK signaling pathway serves a critical role in regulating cell division, proliferation, senescence and apoptosis during physiological and pathological processes, such as adipocyte physiology, insulin signaling, oxidative stress and cancer progression (63)(64)(65)(66). excessive activation of the key molecules of this signaling pathway in the majority of types of cancer results in an unbalanced cell proliferation and apoptosis inhibition or escapement (67,68). Additionally, it has been confirmed that the activation of the RAF/MEK/ERK signaling pathway modulated the role of VEGF in tumor pathogenesis and metastasis (69)(70)(71)(72).…”
Section: Discussionmentioning
confidence: 99%